2011
DOI: 10.1097/ccm.0b013e318225756d
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic exposure and resistance development in Pseudomonas aeruginosa and Enterobacter species in intensive care units*

Abstract: Meropenem exposure is associated with the highest risk of resistance development in P. aeruginosa. Increasing carbapenem use attributable to emergence of Gram-negative bacteria producing extended-spectrum β-lactamases will enhance antibiotic resistance in P. aeruginosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
1
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 15 publications
6
27
1
9
Order By: Relevance
“…However, after controlling for confounding factors and interaction, prior prolonged exposure to carbapenems was the only independent risk factor for ICU acquired CR-GNB. Carbapenems have been identified as a risk factor for CR Gram-negative isolates in previous studies [27][28][29][30]: carbapenem use was independently associated with imipenem-resistance [27]; imipenem exposure was the major risk factor for imipenem-resistant P. aeruginosa [21,28], and also for CR K. pneumoniae isolation [29]. However, there are exceptions to these findings: fluoroquinolones and antipseudomonal penicillins (and not carbapenems) were independent risk factors for CR K. pneumoniae infection elsewhere [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, after controlling for confounding factors and interaction, prior prolonged exposure to carbapenems was the only independent risk factor for ICU acquired CR-GNB. Carbapenems have been identified as a risk factor for CR Gram-negative isolates in previous studies [27][28][29][30]: carbapenem use was independently associated with imipenem-resistance [27]; imipenem exposure was the major risk factor for imipenem-resistant P. aeruginosa [21,28], and also for CR K. pneumoniae isolation [29]. However, there are exceptions to these findings: fluoroquinolones and antipseudomonal penicillins (and not carbapenems) were independent risk factors for CR K. pneumoniae infection elsewhere [31].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored the risk factors for P. aeruginosa antimicrobial resistance in non-critically ill patients [5, 6]. These studies showed that among antipseudomonas antibiotics, meropenem was associated with the highest risk of resistance emergence [4, 7]. The risk factors for emerging antimicrobial-resistant Pseudomonas aeruginosa in the ICU are also worth investigating, especially to answer the question how quick the antibiotic resistance emerges after the exposure to antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…In einer kleineren Studie von 4 Intensivstationen in Deutschland erkrankten 25 % der mit ESBL-positiven Erregern besiedelten Patienten an einer Infektion (Harnwegs-und Wundinfektionen, Pneumonie und Pleuraempyem) [207]. [223]. Auch auf einer neonatologischen Abteilung beeinflusste die Gabe von 3.…”
Section: Neben Patienteneigenenunclassified